(untitled) (Педагогіка вищої та середньої школи, 2010)
The article deals with the question of forming the concepts « method» , «methodology method of teaching» in the pedagogical science. The author conciders the meaning of method as such mediated link of cognitive process which « saves » intelectual and creative offorts of the subject of cognitive activity in the penetrating process of one’s own methodical experience into the previous generalizing experience and favours its conceptualization.